2016
DOI: 10.1002/alr.21872
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy vs continued medical therapy for medically refractory chronic rhinosinusitis: a systematic review and meta‐analysis

Abstract: On meta-analysis, for CRS patients refractory to AMT, ESS significantly improves objective endoscopic scoring outcomes vs continued medical therapy alone. In patients with refractory CRS who have significant reductions in baseline QOL, ESS results in significant improvements. Continued medical therapy appears to maintain outcomes in patients with less severe baseline QOL. Unpooled analysis demonstrates improvement in health utility, olfaction, and cost-effectiveness following ESS compared to continued medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 25 publications
3
41
0
1
Order By: Relevance
“…This reflects both the overall volume of patients utilizing these medications. The highest overall cost reductions were antibiotics (62.9%), followed by antihistamines (50.9%) and anti‐inflammatory agents (36.3%), yielding a total cost reduction across all drug categories of 34.2% or $3.9 M. These results mirror other studies showing similar reductions . Our look at cost effectiveness is intended to address whether the surgery defrays the additional costs and quality metrics associated with management of disease.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This reflects both the overall volume of patients utilizing these medications. The highest overall cost reductions were antibiotics (62.9%), followed by antihistamines (50.9%) and anti‐inflammatory agents (36.3%), yielding a total cost reduction across all drug categories of 34.2% or $3.9 M. These results mirror other studies showing similar reductions . Our look at cost effectiveness is intended to address whether the surgery defrays the additional costs and quality metrics associated with management of disease.…”
Section: Discussionsupporting
confidence: 55%
“…The highest overall cost reductions were antibiotics (62.9%), followed by antihistamines (50.9%) and anti-inflammatory agents (36.3%), yielding a total cost reduction across all drug categories of 34.2% or $3.9 M. These results mirror other studies showing similar reductions. [21][22][23][24][25][26] Our look at cost effectiveness is intended to address whether the surgery defrays the additional costs and quality metrics associated with management of disease. Our assessment specifically focused on metrics such as utilization and costs of prescription drug therapies, and office visits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to measures of fatigue and cognitive function, we sought to use the ctHPQ to assess changes in workplace productivity after initial AMT. Although several studies demonstrated the influence of CRS and its treatment on productivity, they typically examined the effects of continued AMT or surgical therapy as opposed to initial AMT . In the current study we failed to identify changes in absenteeism, presenteeism or relative pressenteeism, and job performance.…”
Section: Discussionmentioning
confidence: 54%
“…3,13 Such data has supported the utility of ESS for the treatment of appropriately selected patients with CRS. 8,11 However, published literature suggests wide variation in costs of ESS ranging from approximately $3,600 2016 USD in Canada, 6,14 to over $10,500 2016 USD in the U.S. 6 This wide variation may be due to much of the cost data for ESS being reported from the perspective of a third party payer, which ultimately reflects charges rather than costs. This also highlights the lack of data on the true costs of ESS and makes it difficult to define the true value of ESS.…”
Section: Introductionmentioning
confidence: 99%